2012
DOI: 10.14710/ijred.1.3.65-73
|View full text |Cite
|
Sign up to set email alerts
|

Design and Economic Analysis of a Photovoltaic System: A Case Study

Abstract: This paper presents the design analysis of a photovoltaic (PV) system to power the CAD/CAM Laboratory at the Department of Mechanical Engineering, University of Port Harcourt. Life cycle cost and break-even point analyses are also carried out to assess the economic viability of the system. The unit cost of electricity for the designed PV system is high compared to the current unit cost of the municipally supplied electricity, but will be competitive with lowering cost of PV system components and favourable gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 10 publications
0
20
0
2
Order By: Relevance
“…The unit cost of electricity was estimated to be 0.74 USD kWh/d. Oko et al [37] designed a stand-alone PV system for Port Harcourt in Nigeria and carried out economic analysis of the proposed system. The authors concluded that sorting the input data in an automated MS Excel (version, manufacturer, city, state abbreviation if USA and Canada, Country) spread sheet would help in performing design and economic analyses of PV systems in any geographical location.…”
Section: Introductionmentioning
confidence: 99%
“…The unit cost of electricity was estimated to be 0.74 USD kWh/d. Oko et al [37] designed a stand-alone PV system for Port Harcourt in Nigeria and carried out economic analysis of the proposed system. The authors concluded that sorting the input data in an automated MS Excel (version, manufacturer, city, state abbreviation if USA and Canada, Country) spread sheet would help in performing design and economic analyses of PV systems in any geographical location.…”
Section: Introductionmentioning
confidence: 99%
“…As this desktop study (Abanda et al, 2016;Akikur et al, 2013;Aravindh and Ganesh, 2016;Azimoh et al, 2016;Baurzhan and Jenkins, 2016;Bhutan Power Corporation Limited, 2018;Chaiporn et al, 2018;Chaurey and Kandpal, 2010;Erin, 2017;Farman et al, 2011;Ghafoor and Munir, 2015;Halder, 2016;Hamed, 2017;Hirsch et al, 2018;Khan et al, 2018;Kulworawanichpong and Mwambeleko, 2015;Lhazom and Thanarak, 2019;Oko et al, 2012;Ruud et al, 2015;Sam and NREL, 2017;Stojanovski et al, 2017;Sunfueltechnology, n.d.;Synergy Enviro Engineers, n.d.;The World Bank, 2017;Wichit et al, 2015;Zubi et al, 2016;Zubi et al, 2017) was carried out using secondary solar resources data only, site surveys and detailed assessment of meteorological and topographical data were outside the scope of this study. Therefore, ground measurements and site-specific surveys or data regarding topography, shading effects (obstructions, etc.)…”
Section: Discussionmentioning
confidence: 97%
“…Where is the daily energy required from the battery, DOD is the permissible depth of discharge, AD is autonomy days, is the ampere-hour efficiency of the battery cell, and is the selected nominal DC voltage of the battery block [2,10]. The values of the factors considered while calculating for battery size are battery loss 0.85, 4-days of autonomy, depths of discharge, DOD -0.8, and battery's nominal voltage.…”
Section: Photovoltaic Component Sizingmentioning
confidence: 99%